Music in Quarantine: Connections Between Changes in Lifestyle, Psychological States, and Musical Behaviors During COVID-19 Pandemic - Terasawa, Hiroko; Matsubara, Masaki; Goudarzi, Visda; Sadakata, Makiko (Frontiers in Psychology, 2021)
Music is not only the art of organized sound but also a compound of social interaction among people, built upon social and environmental foundations. In the long history of human culture, music has provided emotional support and social bonding through performance, listening, and dancing together. Since the beginning of the COVID-19 outbreak, containment measures such as shelter-in-place, lockdown, social distancing, and self-quarantine, have impacted the foundation of human society, resulting in a drastic change in our everyday experience. We investigated the relationships between musical behavior, lifestyle, and psychological states during the shelter-in-place period of the COVID-19 pandemic. We conducted an online survey about the musical experience in early June 2020, asking questions about lifestyle changes, stress levels, musical behaviors, media usage, and environmental sounds. Responses from 620 people in 24 countries were collected. Structural equation modeling analysis revealed causal relationships between lifestyle, stress, and music behaviors. Elements such as stress level change (SLC), work risk, and staying home contribute to changes in musical experiences, such as moderating emotion with music, feeling emotional with music, and more attention to music. SLC is correlated with work risk and income change, while people who started living with others due to the outbreak, especially with their children, indicated a lower stress level change. People with more SLC tended to use music more purposefully for their mental well-being, such as to moderate emotion, to influence mood, and to relax. In addition, people with more SL tend to be more annoyed with neighbors' noise. The housing type was not directly associated with annoyance, however the attention to environmental sounds decreased when the housing type is smaller. Multi-group SEM based on musicianship showed that the causal relationship structure for professional musicians differs from that of less-experienced musicians. For professional musicians, staying at home is the only dominant component that causes all musical behavior changes. Less-experienced musicians tended to have more emotion-related reactions with music. Listening to music via YouTube and streaming was preferred over TV and radio, especially among less-experienced musicians, while participation in the online music community was preferred by more advanced musicians.